Sepsis-driven metabolic reprogramming shapes cancer immunotherapy efficacy, metastatic potential, and drug sensitivity - Wang, Leyi; Wu, Changdong; Hou, Ming; Li, Zhiwei (Frontiers in Immunology, 2025)
Sepsis and cancer interact in a complex, bidirectional manner that significantly impacts patient prognosis, with metabolic reprogramming being a key factor. Sepsis-induced immune dysregulation and metabolic changes promote immunosuppression, tumor growth, metastasis, and resistance to immunotherapy. Cancer patients, especially those on immunosuppressive therapies, are more vulnerable to sepsis, complicating treatment and worsening outcomes. An integrated approach combining immunotherapy, metabolic interventions, and antimicrobial strategies is essential, alongside identifying biomarkers for personalized care. Recent advancements emphasize the need to integrate molecular insights, immunotherapy, and drug sensitivity analysis. This review explores how sepsis-driven metabolic reprogramming affects cancer immunotherapy and metastasis, providing a foundation for future integrated treatment strategies. Further research should focus on developing precise therapies that regulate metabolism, immunity, and the microbiome.